The Implementation of Gamification in Islamic History Learning to Enhance Students' Learning Motivation at SMK PAB 5 Klumpang - Ayudia, Syiera; Arham, Arham; Azmi, Ela Fadilah; Raihan, Muhammad (Yayasan Rahmat Islamiyah, 2025)
This study aims to analyze the implementation of gamification in Islamic History learning and its impact on students' learning motivation at SMK PAB 5 Klumpang. Gamification is a learning approach that integrates game elements such as points, badges, and challenges into the learning process to enhance student engagement and motivation. This research employs a quantitative method with a quasi-experimental design, involving an experimental group that receives gamification-based learning and a control group that undergoes conventional learning. Data were collected through a learning motivation questionnaire and observations during the learning process. The findings indicate that students who participated in gamification-based learning exhibited higher learning motivation levels compared to the control group. Thus, the implementation of gamification in Islamic History learning has proven effective in enhancing students' learning motivation.